2021
DOI: 10.1038/s12276-021-00645-4
|View full text |Cite
|
Sign up to set email alerts
|

Calbindin regulates Kv4.1 trafficking and excitability in dentate granule cells via CaMKII-dependent phosphorylation

Abstract: Calbindin, a major Ca2+ buffer in dentate granule cells (GCs), plays a critical role in shaping Ca2+ signals, yet how it regulates neuronal function remains largely unknown. Here, we found that calbindin knockout (CBKO) mice exhibited dentate GC hyperexcitability and impaired pattern separation, which co-occurred with reduced K+ current due to downregulated surface expression of Kv4.1. Relatedly, manipulation of calbindin expression in HT22 cells led to changes in CaMKII activation and the level of surface loc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…pCaMKII was observed among the pulled-down proteins when GST-MLC1-C-t and the FL protein were used, but not when the assay was performed with the recombinant GST-MLC1-N-t peptide ( Figure 1 G). The MLC1 GST-MLC1-C-t and FL protein also bound the serine/threonine protein phosphatase 1 (PP1) and protein phosphatase 2A (PP2A), ( Figure 1 G) with both enzymes involved in the de-phosphorylation of the CaMKII and of their target proteins [ 37 , 38 ]. In the same experiment, no binding occurred with beta dystroglycan (β-DG), a protein already found not to interact with either the MLC1 N- or C-terminal [ 19 ], and thus used as negative control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…pCaMKII was observed among the pulled-down proteins when GST-MLC1-C-t and the FL protein were used, but not when the assay was performed with the recombinant GST-MLC1-N-t peptide ( Figure 1 G). The MLC1 GST-MLC1-C-t and FL protein also bound the serine/threonine protein phosphatase 1 (PP1) and protein phosphatase 2A (PP2A), ( Figure 1 G) with both enzymes involved in the de-phosphorylation of the CaMKII and of their target proteins [ 37 , 38 ]. In the same experiment, no binding occurred with beta dystroglycan (β-DG), a protein already found not to interact with either the MLC1 N- or C-terminal [ 19 ], and thus used as negative control.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of CaMKII and the consequent CaMKII-mediated phosphorylation can strongly modulate the target protein structural organization, intracellular localization, and functionality [ 38 , 39 ]. To clarify the effects of CaMKII-mediated phosphorylation on MLC1 structural and functional properties, we generated two U251 cell lines, where the CaMKII phosphorylation site T17 was mutated into (i) alanine (T17A), a non-phosphorylatable amino acid, or (ii) aspartic acid (T17D), an amino acid mimicking protein constitutive phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Exploring the correlation between calbindin expression and neuronal excitability, as well as ion channel expression, has been a focus in various cellular models. For example, it has been shown that dentate granule cell excitability is increased in a calbindin-D28K knockout mouse model [17], an effect attributed to a reduction in voltage-gated potassium currents. Similarly, calbindin-D28K expression in a rat beta-cell line results in a reduction of voltage-gated calcium currents [18].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, calbindin-D28K protein expression has been correlated with distinct neuronal excitability properties. For instance, calbindin-D28K expression has been linked to alterations in neuronal action potential frequency [15, 17]. Additionally, Calbindin-D28K expression has also been associated with changes in the activity of ionic channels, such as voltage-gated calcium or potassium channels [17, 18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation